The Effect of Proctodeal Gland Foam, Diluent and Dimethylacetamide Addition on Morphology and Fertilising Ability of Japanese Quail (Coturnix japonica) Spermatozoa - Bronislawa Chelmonska; Ewa Lukaszewicz; Artur Kowalczyk; Anna Jerysz (The Journal of Poultry Science, 2006)
The effect of proctodeal gland foam addition to fresh net or diluted semen supplemented with (DMA) dimethylacetamide, on morphology and fertilising potency of quail spermatozoa was evaluated. Every stage of quail semen preparation caused an increase in sperm deformations. The addition of foam, diluent and DMA decreased the number of morphologically intact spermatozoa by 28.3 percent points, in relation to the fresh semen. Foam addition to the fresh semen allowed to obtain 91.4% fertility, which was similar to results obtained during natural mating (93.0%), but in diluted and DMA supplemented semen, equilibrated for 5 minutes at 4°C, the foam had a detrimental effect on fertilising ability of spermatozoa.